Percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy - Bunc Matjaz; Steblovnik Klemen; Zorman Simona; Popovic Peter (Radiology and Oncology, 2020)
High-risk pulmonary embolism is associated with a high early mortality rate. We report our experience with percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy.